Effects of crude glycerin levels on nutritional characteristics and performance of sheep fed mixed forage diets - Alessandra Schaphauser Rosseto Fonseca; Inácio Martins da Silva Neto; Matheus Lima Corrêa Abreu; Ana Cláudia da Costa; Karine Padilha Nunes Vieira; Laura Barbosa de Carvalho; Rosemary Lais Galati; Farah Arruda Petter; Luciano da Silva Cabral (Revista Brasileira de Zootecnia)
ABSTRACT Two studies were carried out to investigate the effects of crude glycerin (CG) levels in feedlot sheep diets as a substitute for ground corn. In the first study, four castrated rumen-canulated sheep were used to assess the effects of CG on nutrient intake, digestibility, rumen characteristics, and blood glucose. In the second study, 40 crossbred female lambs were employed to evaluate the influence of CG levels in the diet on nutrient intake, digestibility, and animal performance. Crude glycerin levels did not affect nutrient intake in either study, except for crude fat (CF) intake, which increased linearly as neutral detergent fiber decreased. However, the digestibility of dry matter, CF, total carbohydrates, and non-fibrous carbohydrates increased linearly, with CF being quadratically affected in both studies. Rumen pH (mean = 6.1) and blood glucose (mean = 61.72 mg/dL) remained unaffected by CG levels, whereas ruminal ammonia nitrogen displayed a quadratic response. Additionally, CG levels did not impact the performance (mean = 204.6 g/d) in female feedlot lambs, suggesting that CG can be included in sheep diets at up to 30% in a mixed forage diet.